Experimental realization and performance evaluation of refractive index SPR sensor based on unmasked short tapered multimode-fiber operating in aqueous environments - Al-Qazwini, Yusser; Noor, A.S.M.; Yaacob, M.H.; Harun, Sulaiman Wadi; Mahdi, M.A. (Elsevier, 2015)
In this work, we fabricate and characterize an SPR sensor based on unmasked short tapered multimode fiber. The entire taper region is coated with gold without masking offering a simpler approach towards the sensor fabrication. The sensor was tested by immersion in sensing solutions of different refractive indices and the transmittance is measured using a spectrometer system. The sensor performance in terms of sensitivity, detection accuracy, and robustness can be controlled by adjusting the taper physical parameters such as waist diameter, waist length, and transition length. We realize a compact, sensitive, cost-effective and robust SPR sensor suitable for aqueous media sensing by reducing the waist diameter up to 25-45 mu m with a total taper length of 3-5 mm coated with a thin gold film of around 55 nm. The demonstrated sensor exhibits a sensitivity of 1600-2000 nm/RIU and a full width at half maximum (FWHM) of 140-220 nm. (C) 2015 Elsevier B.V. All rights reserved.